Technology-based and supervised exercise interventions for individuals with type 2 diabetes: Randomized controlled trial - Timurtas, Eren (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2022)
• DIABETEX mobile app showed evidence in controlling glycemic control. • Wearable smartwatches also showed evidence in reducing HbA1c. • Technology supported exercise regimens are as equally safe and effective as in-person programs in diabetes management. • mHealth is a promising delivery method to improve health outcomes in people living with diabetes or with other chronic conditions.